Women design their own vaginal microbicide trial: Suggestions on how to improve adherence from former participants of HIV prevention trials. - Lori Miller; Neetha Morar; Saidi Kapiga; Gita Ramjee; Richard Hayes (PLoS ONE)
Low adherence in vaginal microbicide clinical trials for HIV prevention has impeded interpretation of trial results and hindered evaluation of potentially efficacious HIV prevention gels. Understanding the underlying reasons why women join trials and their barriers to product use can support identification of ways to improve adherence and its reporting. Eight focus group discussion workshops were conducted with 46 former microbicide trial participants in Durban, South Africa and Mwanza, Tanzania. Participants provided feedback on why women join trials, the barriers to using study gel and reporting adherence accurately, and how clinical trial design can be improved to support better adherence and its reporting. Women join microbicide trials for a number of important reasons such as healthcare and financial reimbursement. Fear of adverse effects from the investigational product was the most important reason why participants reported not using the gel. The key reason for inaccurate reporting of gel use was fear of removal from the trial. Participants made concrete suggestions for improving microbicide trial design such as applicator use testing and real time feedback, improving education to participants about how trials answer their research questions, and improving transparency and clarity about study procedures. Participants also gave feedback on an innovative trial design with a non-randomised arm. Identifying HIV prevention products for women requires better understanding of the lives of women asked to join these trials, and application of that understanding to microbicide trial design. This study has demonstrated that participants and research teams can work collaboratively to design clinical trials that meet needs of both the research and of participants.